2004
DOI: 10.1007/s00125-004-1597-y
|View full text |Cite
|
Sign up to set email alerts
|

The prospective association between adiponectin and coronary artery disease among individuals with type 1 diabetes. The Pittsburgh Epidemiology of Diabetes Complications Study

Abstract: Aims/hypothesis: Recent findings suggest the potential involvement of adiponectin in obesity, diabetes and cardiovascular disease. We assessed the prospective association between adiponectin concentration and coronary artery disease in individuals with type 1 diabetes. Methods: Participants were identified from the Pittsburgh Epidemiology of Diabetes Complications cohort, a prospective follow-up study of childhood-onset type 1 diabetes. At baseline, subjects had a mean age of 28 years, and a mean diabetes dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
2
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(90 citation statements)
references
References 50 publications
5
79
2
4
Order By: Relevance
“…This study has demonstrated, as have other studies in adults with type 1 diabetes (12,(23)(24)(25), that serum concentrations of adiponectin are elevated in children and adolescents with type 1 diabetes. In contrast to adults, studies in children and adolescents with type 1 diabetes show controversial results (26,27).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…This study has demonstrated, as have other studies in adults with type 1 diabetes (12,(23)(24)(25), that serum concentrations of adiponectin are elevated in children and adolescents with type 1 diabetes. In contrast to adults, studies in children and adolescents with type 1 diabetes show controversial results (26,27).…”
Section: Discussionsupporting
confidence: 84%
“…This observation is confirmed by the paediatric studies where gender differences were not seen either (26,27). In contrast, the published studies in adults report on higher levels of adiponectin in women (12,(23)(24)(25). However, the findings in this study regarding the differences between adiponectin levels in males and females during pubertal development suggest an influence of gender.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…CRP as a measure of inflammation by high sensitivity CRP measurement (Dr. Russell Tracy, University of Vermont) (27) and measures of adiponectin (31,32) and insulin (33) at the Heinz Nutrition Laboratory at the University of Pittsburgh, Graduate School of Public Health (Dr. Rhobert Evans).…”
Section: Measurements On Stored Serum Specimensmentioning
confidence: 99%